Evolution of the Continental Crust in the Northern Tibetan Plateau: Constraints From Geochronology and Hf Isotopes of Detrital Zircons - Liu, Zeyu; Zhang, Guibin; Xiong, Lu; Chang, Feng; Liu, Shuaiqi (Frontiers in Earth Science, 2022)
To investigate the evolution of the continental crust in the northern Tibetan Plateau, detrital zircon U–Pb geochronology and Hf isotopes analysis were performed on two fluvial sand samples from North Qaidam (the Yuka and Shaliu rivers). A total of 443 detrital zircon U–Pb ages and 244 Hf isotopic results were obtained and reveal that the South Qilian, North Qaidam, and East Kunlun terranes show affinity to the western Yangtze Block. Age distributions of detrital zircons from the Yuka River cluster mainly in two age intervals of 1000–700 and 480–400 Ma. The corresponding εHf(t) values are mostly negative, with depleted two-stage Hf model ages (TDM2) of 2.1–1.6 Ga. In contrast, age data for the Shaliu River fall in the ranges of 1000–700, 460–380, and 260–200 Ma, with TDM2 ages of 2.0-1.6 and 1.6–1.2 Ga. In addition, zircons with Neoproterozoic ages from both river samples possess common Paleoproterozoic TDM2 ages (2.0–1.6 Ga, with a peak of 1.8–1.7 Ga), indicating that the South Qilian, North Qaidam and East Kunlun terranes were probably part of the same Neoproterozoic continent. The East Kunlun and North Qaidam terranes are inferred to include Mesoproterozoic continental crust (1.6–1.0 Ga), suggesting differences in crustal evolution between the East Kunlun–North Qaidam and Qilian terranes. Phanerozoic magmatism in these three terranes was sourced mainly from the recycling of ancient continental crust with minor contributions from the juvenile crust.